Cities, cultural policy and governance - Anheier, Helmut K., 1954-; Isar, Yudhishthir Raj.; Hoelscher, Michael (Los Angeles, [Calif.] ; London : SAGE, 2012)
The fifth volume in the cutting edge'Cultures and Globalization Series', this volume explores a city's cultural dynamics and its impact on policy including alternative economies, creativity migration, diversity, sustainability, education and urban planning.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Culture and globalization; Sociology, Urban; Cultural policy